2016
DOI: 10.3847/1538-4357/833/2/190
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Spectroscopy of Nearby Seyfert Galaxies: Is There Evidence for Shock Excitation in Narrow-Line Regions?

Abstract: One of the unsettled, important problems in active galactic nuclei (AGNs) is the major ionization mechanism of gas clouds in their narrow-line regions (NLRs). In order to investigate this issue, we present our J-band spectroscopic observations for a sample of 26 nearby Seyfert galaxies. In our study, we use the flux ratio of the following two forbidden emission lines, [Fe ii]1.257µm and [P ii]1.188µm because it is known that this ratio is sensitive to the ionization mechanism. We obtain the [Fe ii]/[P ii] flux… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 108 publications
1
12
0
Order By: Relevance
“…As noted by others (Schlesinger et al 2009), we do not see any evidence for shock ionization in the outflow regions (see, e.g. Schlesinger et al 2009;Maksym et al 2016Maksym et al , 2017Terao et al 2016, and references therein for dis- cussions on shocks). Our composite models qualitatively agree with the IUE UV line ratios, indicating that we are likely encompassing a significant portion of the UV emitting gas in our models and resulting outflow rates.…”
Section: Model Comparison To the Observationssupporting
confidence: 74%
“…As noted by others (Schlesinger et al 2009), we do not see any evidence for shock ionization in the outflow regions (see, e.g. Schlesinger et al 2009;Maksym et al 2016Maksym et al , 2017Terao et al 2016, and references therein for dis- cussions on shocks). Our composite models qualitatively agree with the IUE UV line ratios, indicating that we are likely encompassing a significant portion of the UV emitting gas in our models and resulting outflow rates.…”
Section: Model Comparison To the Observationssupporting
confidence: 74%
“…In our 1.5 − 8.0 annular region, however, we find a thermal component that may be associated with fast shocks. This is not necessarily inconsistent with the Terao et al (2016) results, since nonradiative, fast shocks would not be observed in the optical/IR. The photoionization parameters from our best fits also provide constraints on the presence of highly ionized outflows, such as warm absorbers (WAs), in NGC 7212.…”
Section: Physical Modelsmentioning
confidence: 52%
“…Marconi et al 2000;Krajnović et al 2007). The sharp rise of the [Fe II]/[P II] ratio with apertures up to 1.25 (Krajnović et al 2007) suggests an increasingly dominating shock contribution (see Terao et al 2016). In addition, the high surface brightness of the 1−0 S (1) (Israel et al 1990 (Sturm et al 2002;Ogle et al 2010) is likewise characteristic for shock excitation and incompatible with the PDR models of Kaufman et al (2006) for any reasonable combination of density n • and radiation field G. At least the [S III] flux originates in a region less than 11 across, excluding emission from either the outer CND or the outflow.…”
Section: Shocked Molecular Gas In the Centermentioning
confidence: 97%